Workshop 2023 parliamentary and presidential elections in Turkey - Torosyan, Veronika (ՀՀ ԳԱԱ Արևելագիտության ինստիտուտ)
The workshop, held on May 8, 2023, at the Institute of Oriental Studies of the NAS RA, was devoted to the parliamentary and presidential elections in Turkey.
Keywords: Workshop; Elections